The availability and functionality of medical equipment and the barriers to their use at comprehensive specialized hospitals in the Amhara region, Ethiopia - Woldeyohanins, Alem Endeshaw; Molla, Nigatu Mihretu; Mekonen, Abibo Wondie; Wondimu, Abrham (Frontiers in Health Services, 2025)
BackgroundPublic healthcare practices, particularly disease prevention, screening, diagnosis, treatment, and rehabilitation of patients, heavily rely on the availability and functionality of medical equipment. The absence of sufficient medical equipment and the malfunctioning of existing equipment impede the ability to provide effective healthcare services and directly affect patient rehabilitation, while the challenges related to medical equipment utilization are huge, especially in countries with limited resources such as Ethiopia. Therefore, this study aimed to assess the availability, functionality, and barriers associated with the use of medical equipment at public comprehensive specialized hospitals in Amhara Regional State, Ethiopia.MethodsA cross-sectional study design involving both quantitative and qualitative methods was conducted. Eight (n = 8) comprehensive specialized hospitals in the Amhara region were selected purposefully and included in this study. The data used to assess the availability and functionality of medical equipment items (n = 78) listed by the Ethiopian Ministry of Health that are supposed to be available in all of the comprehensive specialized hospitals were collected from 29 May to 18 June 2023. Self-administered structured questionnaires, observational checklists, and key informant interview guides were used to collect the necessary data. To analyze the quantitative data, descriptive statistics were employed, and qualitative data were analyzed using a thematic approach.ResultsThe study revealed that the availability of medical equipment in at least one hospital was 55.93% on average, and the availability of at least one piece of medical equipment in the surveyed hospitals was only 25.6%. The overall functional status of medical equipment was 74.68%. The present study also indicated that 75% of the surveyed facility's biomedical engineers did not receive on-the-job training regularly. Of the eight surveyed facilities, only one had spare parts and accessories for their medical equipment and the majority (87.5%) of the facilities did not have enough medical equipment storage space and did not have medical equipment policies. The qualitative findings of this study showed that issues with the utilization of the Medical Equipment Management Information System, a lack of spare parts and accessories, the absence of a well-equipped and standardized maintenance workshop, and insufficient operator training were the major challenges.ConclusionThis study revealed critical deficiencies in medical equipment availability, functionality, and barriers to maintenance at the surveyed facilities. Therefore, to improve healthcare service delivery, collaborative efforts and targeted interventions are essential in optimizing the availability and functionality of medical equipment at each and every health facility.